BC Reads Adult Literacy Fundamental English Course Pack 5 - Ivits, Shantel; Open Textbook Library (Open Textbook Library, 2015)
This course pack is designed to meet the learning outcomes for Adult Literacy Fundamental English Level 5 (roughly equivalent to grades 6 to 7.5 in the K-12 system). Every chapter includes a level-appropriate, high-interest reading of between 500 and 800 words. The readings are freely available in a separate reader with convenient links to the readings in each chapter of this course pack. Font size and line spacing can be adjusted in the online view, and have been enhanced for the print and PDF versions for easier reading. This course pack has been reviewed by subject experts from colleges and universities.
The Most Amazing Structure on Earth -- The Many Faces of Genius -- The Many Pathways to Knowledge -- Boost Your Brainpower -- Memory Magic -- Put to the Test -- The Sixth Sense: Intuition -- The Big Five: Personality -- Secrets of a Happy Brain
In English.
Description based on print resource
Keywords: Humanities -- Textbooks; Rhetoric -- Textbooks